2019
DOI: 10.1002/slct.201803680
|View full text |Cite
|
Sign up to set email alerts
|

Metal Telluride Nanomaterials: Facile Synthesis, Properties and Applications for Third Generation Devices.

Abstract: From the material science community, metal telluride semiconductor nanostructures have lately attracted a significant quantity of attention. On account of physics associated in quantum confinement, remarkable surface chemistry metal telluride became the most explored group of semiconductor nanomaterials. The intensive concern in this area originates from their exceptional optical, chemical and electronic properties which give rise to their potential use in the field of solar energy conversion, nonlinear optics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 184 publications
(166 reference statements)
0
18
0
Order By: Relevance
“… 1 Composition, stability, size and shape are among those factors on which the physicochemical properties of nanomaterials have been found to depend. 1 In this regard, metal chalcogenide nanomaterials 1–3 have attracted the attention of researchers increasingly due to their various applications in energy conversion, storage and electronics, 2–5 development of materials for semiconductors, 6–8 dye-sensitized solar cells, 9,10 magnesium–air batteries, 11 aerogel fabrication, 12 and catalysis. 13–20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Composition, stability, size and shape are among those factors on which the physicochemical properties of nanomaterials have been found to depend. 1 In this regard, metal chalcogenide nanomaterials 1–3 have attracted the attention of researchers increasingly due to their various applications in energy conversion, storage and electronics, 2–5 development of materials for semiconductors, 6–8 dye-sensitized solar cells, 9,10 magnesium–air batteries, 11 aerogel fabrication, 12 and catalysis. 13–20 …”
Section: Introductionmentioning
confidence: 99%
“…Among different metal chalcogenides reported in literature, significant work has been done in recent past on the exploration and development of binary phases of tellurides of various metals (excluding palladium), mainly due to their potential application 2 in memory devices, photovoltaic cells, thermoelectrics, biochemical applications, semiconductors with enhanced thermoelectric properties in nanocomposites, photothermal therapy, thin films and nanomaterials and catalysis. 2,4,18–20 After the discovery of easy methods of preparation 16,17,21 of binary phases of palladium selenide and their role in catalysis, 16,17 there has been an enormous increase during last five years on the discovery of interesting applications of palladium selenides 3,9–14 in various fields including catalysis. Binary phases of palladium tellurides are also envisaged to be among applied nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional structures including nanofibers, nanorods, or nanowire can modify the properties. An enhancement of the ZT in one-dimensional Ag 2 Te has been reported [42,43] and was attributed to modified phonon scattering [44,45] and electronic contribution [46]. Such one-dimensional structures of Ag 2 Te have also been applied to flexible thermoelectric [47,48] and electronic [49] devices.…”
Section: Introductionmentioning
confidence: 97%
“…The one-dimensional Ag 2 Te nanostructures have been fabricated mostly via chemical solution synthetic routes [42][43][44][45][46][47][48][49][50][51] such as electrochemical transformation in an electrochemical solution from Ag nanofibers to Ag 2 Te nanotubes [52], possibly because chemical solution synthetic routes were potentially mass-producible and low cost. On the other hand, dry or vacuum-deposition processes such as evaporation, sputtering, and chemical vapor deposition have been little used despite their advantages for avoiding contamination and their high purity.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurides of heavy metals, as well as complex phases and composites based on them, are promising functional materials for electronic engineering [1][2][3][4]. Recent studies have shown that many binary and complex tellurides with tetradimite-like layered structure are topological insulators and can be used in spintronics and quantum computing [5][6][7].…”
Section: Introductionmentioning
confidence: 99%